MutT-related proteins are novel progression and prognostic markers for colorectal cancer - Li, Jin (Oncotarget, 2017)
BACKGROUND: MutT-related proteins, including MTH1, MTH2, MTH3 and NUDT5, can effectively degrade 8-oxoGua-containing nucleotides. The MTH1 expression is elevated in many types of human tumors and MTH1 overexpression correlates with the tumor pathological stage and poor prognosis. However, the expression of other MutT-related proteins in human cancers remains unknown. The present study systematically investigated the expression of MTH1, MTH2, MTH3 and NUDT5 in human colorectal cancer to establish its clinical significance. METHODS: Amounts of MutT-related mRNA and protein in CRC cell lines were assessed by qRT-PCR and Western blotting, respectively. Furthermore, the MutT-related protein expression was evaluated by immunohistochemical staining of tissue microarrays containing 87 paired CRC tissues and by Western blotting of 44 CRC tissue samples. Finally, the effect of knockdown of MutT-related proteins on CRC cell proliferation was investigated. RESULTS: The expression of MTH1, MTH2, MTH3 and NUDT5 was significantly higher in CRC cells and CRC tissues than normal cells and tissues, and this phenomenon was significantly associated with AJCC stage and lymph node metastasis of CRC specimens. CRC patients with high expression of MTH1, MTH2 or NUDT5 had an extremely poor overall survival after surgical resection. Notably, NUDT5 was an independent prognostic factor of CRC patients. We found that knockdown of MutT-related proteins inhibited CRC cell proliferation. CONCLUSIONS: We showed for the first time that MutT-related proteins play an important role in CRC progression and prognosis. Further investigations are needed to elucidate the role of these proteins in CRC progression and their potential use for therapeutic targets.